Hubungan Antara Aktivitas Shalat Lima Waktu Dan Tingkat Stres Pada Siswa SMA Kelas XII Di SMAN 9 Jakarta Tahun 2020 - Mohammad Ali; Restu Arya Pambudi; Talitha Ragilia Sani (Jurnal Fisioterapi dan Kesehatan Indonesia, 2021)
Background: High school class XII students is a period where the burden of curriculum increases, preparation for various kinds of examinations, demands for grades and graduation and it can cause stress. Stress is a physical and psychological response to stressors faced, both from within and from outside the individual. One way to reduce stress is by relaxing therapy and prayer can be an alternative to psychotherapy. The purpose of this study is to determine the correlation between the activity of five daily prayers and stress levels in high school students of class XII at 9 SHS Jakarta. Method: The design of this study was cross sectional. The number of respondents 106 people were selected by purposive sampling. Data collection techniques by filling out questionnaires and measuring stress using DASS-42. Bivariate data analysis uses chi-square. Result: Chi-square test results between prayer activities and stress levels showed a p-value of 0.001, with p <α = 0.05 and the 2x2 table shows an odds ratio score of 10,066. Conclusion: The results show that the activity of the five daily prayers has a significant correlation to the level of stress in high school students class XII with a risk factor 10,066 greater in students who do not perform prayer activities.